THE ENZYMATIC CONVERSION OF EXOMETHYLENE CEPHALOSPORIN-C INTO DEACETYL CEPHALOSPORIN-C AND THE ROLE OF MOLECULAR-OXYGEN IN CEPHALOSPORIN-C BIOSYNTHESIS - Baldwin, J; Adlington, R; Crouch, N; Schofield, C (1988)
Cell free extracts from Cephalosporium acremonium containing deaoetoxy/-deacetyl cephalosporin C Synthetase activities have been shown to convert Exomethylene cephalosporin C directly to deacetyl cephalosporin C. Labelling experiments in the presence of 13O2, indicated the source of the 3-methylene-oxygen of the latter was dioxygen.1. © 1988.